IDENTIFICATION AND ANTIMICROBIAL SUSCEPTIBILITY TESTING OF PATHOGENIC MICRO-ORGANISM FROM DENTAL PATIENTS - M, Sakthivel; Pm, Ayyasamy; Prasanth D, Arvind (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To isolate and identify aerobic microbes present in the periodontal infected patients and to evaluate the choice of antibiotics in the management of periodontal diseases. Methods: In this study, these patients have not been treated previously for their conditions. An informed consent was obtained from these patients before collection of an oral swab. This study was approved by the Institutional Ethical Committee. The details of the patient's age, sex, and clinical details were recorded on a per forma meant for this study. The following methodologies were adopted for the isolation and identification of the microorganisms from these cases. Results: In this study out of 50 oral samples, culture positivity was recorded in 43 (86%) cases and no growth in 7 (14%) cases. Antibiotic susceptibility test using to identified as resistant, sensitive, intermediate of pathogenicity of oral microbes. Such antibiotics were methicillin, ceftazidime, clindamycin, amikacin, cloxacillin, and cefotaxime. This study should be kept in mind when a local application of antibacterial compounds is used in the therapy of periodontal disease. Conclusion: This study highlights the different organisms involved in the different types of dental infections. The antibiotic pattern shown in this work will be a guide to the clinician in the selection of proper antibiotics for the treatment of these infections. Hence in this study, the limitations were time and the number of patients. For better outcomes, a larger study population for a longer period of time should be undertaken to know the bacteriology and to the select the effective drugs of choice for dental infections. A comparative study of bacteriology and mycology and its antimicrobial property would be very fruitful in the future. Keywords: Dental, Periodontal, Bacteria, Antibiotics.